Desenvolvimento de revestimento comestível a base de zeína e blenda de óleos essenciais para aplicação em moçarela - Pereira, Lívio Antônio Silva (2016)
The search for natural preservatives, allied to the higher quality and durability of food, creates the need for biodegradable and food quality optimizing packaging. Edible coatings are currently being studied and are a part of a promising future in the field of food. The use of biopolymer packaging with additives, such as essential oils, are constantly objects for researches, due to its antimicrobial properties and for acting as substitute for preservatives. In this study, we evaluated zein as biopolymeric matrix and a blend of garlic and thyme essential oil as plasticizer, flavoring and antimicrobial agent. By means of this coating, applied mozzarellas with different contents of sodium, the antimicrobial and flavoring properties, and consumer acceptance, were evaluated. We verified effective plasticizing action of the essential oils over zein films from the concentration of 3% (v/v). There was good antimicrobial action of the zein films and garlic and thyme essential oil blend with the addition of 2% (v/v) of oils, regarding bacteria Enteropathogenic Echerichia coli, Listeria monocytogenes, Salmonella Enteretidis and Staphylococcus aureus. Concerning the mozzarella with 3% (v/v) of oil blend, we verified a decrease in water loss of up to 50%, efficacy potential in the control of mesophle aerobic microorganisms, fungi and yeast. In sensorial analyses, we verified good acceptance of sodium reduction up to 75% of the standard. The plasticizing action of the essential oil blend in the zein matrix can be proven by means of eliminating cracks and reducing the rigidity of the films. We also found good antimicrobial efficiency for the tested microorganisms. In conclusion, the zein based films and essential oil blend are affected by the addition of essential oil blend, altering the engineering and antimicrobial properties and acting efficiently in reducing sodium from the mozzarellas.